CONSUMERS’ PERCEPTION ABOUT MEAT TYPES AMONG STUDENTS OF THE UNIVERSITY OF AGRICULTURE ABEOKUTA, OGUN STATE (FUDMA JOURNAL OF SCIENCES, 2023)
This study carried out the Analysis of Consumers’ Perception about Meat Types among Students of the University of Agriculture Abeokuta Ogun State. The study utilized primary data collected from 150 students of the University through the administration of questionnaire. A stratified random sampling technique wasutilized to sample students from each level of 100-500 and post graduate level in which 25 students were selected from each level. The data collected were analyzed with descriptive statistics, a seven point likert-scale. The mean monthly expenditure on meat types revealed that beef (N462), chicken (N399) and fish (N294) represent 24.22%, 20.94% and 15.38% percentage respectively of the income of the students. In terms of perception of various meat types by taste, chicken was the most preferred with a mean of 5.58, perception by nutritional content and cholesterol level revealed that fish was most preferred with a mean of 6.31 while pork was least preferred with a mean of 6.42. Results also revealed that in terms of economic value and ease of cooking turkey and fish were most preferred protein sources. In terms of overall preference, beef was most preferred among the students. Based on the findings, it is therefore recommended that there is a need to increase the supply of beef, chicken and fish in shops close to students’ residence as they were found to be the most important meat types consumed
Keywords: consumer choice, meat types, university students, consumer perception, most consumed